barriers to oceanic island radiation in bryophytes: insights from the phylogeography of the moss Grimmia montana - Vanderpoorten, Alain; Devos, Nicolas; Goffinet, Bernard; Hardy, Olivier J; Shaw, A. Jonathan (Journal of biogeography, 2008)
In contrast to angiosperms, bryophytes do not appear to have radiated in Macaronesia and the western Mediterranean. We evaluate if: (1) the apparent lack of radiation in bryophytes reflects our failure to recognize cryptic endemic species; (2) bryophytes are characterized by extremely low evolutionary rates; or (3) bryophytes have a high dispersal ability, which prevents genetic isolation. Worldwide, with a special emphasis on Macaronesia and the western Mediterranean. Three chloroplast regions were sequenced from samples of the moss Grimmia montana from its entire distribution range. Network analyses, Fst and Nst statistics were used to describe and interpret the phylogeographical signal in the data. Despite significant phylogeographical signal in the chloroplast genome, which demonstrates limits to gene flow at the continental scale, repeated sister group relationships observed among accessions from different geographical areas suggest recurrent colonization patterns. These observations are consistent with mounting evidence that intercontinental distributions exhibited by many bryophyte species result from long-distance dispersal rather than continental drift. Madeiran and western Mediterranean island haplotypes are either shared by, or closely related to, European and North American ones. Fst values between Madeira, western Mediterranean islands, North America and Europe are not significantly different from zero, and suggest that Madeira and the south-western Mediterranean are subject to strong transatlantic gene flow. By contrast, haplotypes found in the Canary Islands are shared or closely related to those of populations from south-western Europe or southern Africa. Multiple origins and colonization events are not consistent with the hypothesis of a relictual origin of the Macaronesian moss flora. One possible reason for the failure of taxa that experienced multiple colonization events to radiate is niche pre-emption. We suggest that strong gene flow, coupled with the occupancy of all suitable niches, either by earlier conspecific colonizers or by other species, could be the mechanism preventing island radiation in G. montana and other cryptogams with high long-distance dispersal abilities.